The influence of postpartum depression literacy on health promoting behaviors among postpartum women - Zhihui Chen; Chuntao Liu; Xiaojing Tan; Xiaoli Liao (Scientific Reports)
Abstract This study aimed to investigate the influence of postpartum depression literacy on health promoting behaviors among postpartum women, focusing on the mediating role of self-efficacy and the moderating effect of family functioning in this dynamic relationship. A cross-sectional survey was conducted with 622 postpartum women recruited during routine prenatal visits. Data were collected using validated instruments, including the Postpartum Depression Literacy Scale, Health-Promoting Lifestyle Profile II, General Self-Efficacy Scale, and Family Adaptability and Cohesion Scale. A moderated mediation model was adopted to examine direct, indirect, and interaction effects among the variables. Higher levels of postpartum depression literacy were significantly associated with increased engagement in health promoting behaviors. Self-efficacy partially mediated this relationship, with an indirect effect size of 0.35, indicating its central role in translating mental health literacy into positive behavioral outcomes. Family functioning moderated the association between postpartum depression literacy and self-efficacy, with stronger family support amplifying the beneficial effect (interaction effect, p < 0.05). These findings indicate that postpartum depression literacy significantly contributes to the adoption of health promoting behaviors among postpartum women, primarily by enhancing self-efficacy, a mechanism that is further reinforced in the context of high family functioning. This underscores the necessity of incorporating both mental health literacy enhancement and family-centered support strategies into comprehensive maternal health promotion programs to maximize behavioral engagement and improve overall maternal well being.